Genotoxicity induced by nerol, an essential oil present in citric plants using human peripheral blood mononuclear cells (PBMC) and HepG2/C3A cells as a model - Silva, Brian Ogushi [UNESP] (2021)
Nerol (cis-3,7-dimethyl-2,6-octadien-1-ol) is a monoterpene widely used in cosmetic products, household detergents and cleaners, as well as a flavoring in several food products. Despite the high level of human exposure to nerol, an absence of studies regarding potential genetic toxicity in human cells exists. The aim of this investigation was to examine the cytotoxic and genotoxic potential of this monoterpene on human peripheral blood mononuclear cells as well as hepatic metabolizing HepG2/C3A human cell line. Cytotoxicity was assessed using trypan blue staining and MTT assay while genotoxicity was determined utilizing the comet and micronucleus test. Cytotoxicity tests showed cell viability greater than 70% for concentrations between 2.5 and 500 µg/ml. Both cell types exhibited significant DNA damage and chromosomal mutations after medium and high concentration incubation with nerol indicating that the safety of use of this monoterpene in various formulations to which humans are exposed needs to be monitored and requires more comprehensive investigations.